On the role of structural variables in magnetic properties of Co(1-x)NixFe2O4 nanoferrites. Issue 16 (November 2019) - Ebrahimi, F.; Sajjadi, S.A.; Babakhani, A.
Abstract: In the present study, Co(1-x) Nix Fe2 O4 nanoferrites were successfully synthesized through reverse microemulsion technique. Furthermore, the effect of size, morphology as well as chemical composition (x = 0, 0.25, 0.5, 0.75, 1) were evaluated in detail on the magnetic properties of the nanoferrites. The selected system was water/CTAB/1-hexanol which was based on the microemulsion ternary phase diagram. The particle size and morphology were controlled by altering the proportion of microemulsion compositions. Phase composition and morphology of the resultant samples were studied by X-ray diffraction (XRD), atomic absorption spectroscopy (AAS), transmission electron microscopy (TEM) and atomic force microscopy (AFM). In addition, in order to characterize the magnetic properties of the specimens, vibrating sample magnetometer (VSM) were utilized. The results showed that the magnetic properties were strongly affected by the size, morphology and chemical composition of the samples. In the case of spherical nanoparticles, it was found that with increasing particle size from 3 nm to 10 nm the saturation magnetization increased from 17 emu/gr to 30 emu/gr with perfect superparamagnetic behavior. It is worth mentioning that flaky-nanoferrites were synthesized, for the first time, in this research. By changing the morphology from sphere to flake, the magnetic behavior was varied from perfect superparamagnetic to ferromagnetic. In the case of flaky particles, the saturation magnetization and coercivity were measured around 7.5 emu/gr and 120 Oe as well as 12 emu/gr and 625 Oe for the lower and higher aspect ratio, respectively. Finally, comparing the chemical composition of the samples, it was observed that the CoFe2 O4 nanoparticles have the greatest value of saturation magnetization ( 53 emu/gr), while the NiFe2 O4 nanoparticles showed the lowest value of 6.5 emu/gr.